Water matrices as potential source of SARS-CoV-2 transmission – An overview from environmental perspective - Bilal, Muhammad (Case Studies in Chemical and Environmental Engineering, 2020)
Evidently, the emergence of novel coronavirus disease (COVID-19) caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) has rapidly blowout across the world. Since, the presence of coronaviruses, including SARS-CoV-2 in the fecal specimens and anal swabs of some infected patients, has raised emerging concern with the likelihood of fecal-based spread must be inspected and clarified. Therefore, herein, an effort has been made to spotlight the current scenarios and possible solutions to better understand the risks associated with the wastewater matrices as a potential source of SARS-CoV-2 transmission in the environment. The information reviewed here constitutes a paramount intellectual basis to sustenance ongoing research to tackle the SARS-CoV-2 issue. Thus, this overview indicates the most accessible frontiers related to the detection, quantification, and possible transmission of SARS-CoV-2 in the environment through water routes. The regulatory authorities and policymakers must assure the society via dissemination of evidence-based guidelines that the water matrices, including groundwater and drinking water resources are safe. Finally, we have identified and enlisted a number of pressing questions concerning the ongoing SARS-CoV-2 transmission or COVID-19 emergence issue that must be carefully answered to put further and deeper insight into SARS-CoV-2/COVID-19 in future studies.